2019
DOI: 10.1088/1748-605x/ab0d69
|View full text |Cite
|
Sign up to set email alerts
|

Gliosis of astrocytes cultivated on coral skeleton is regulated by the matrix surface topography

Abstract: Astrogilosis is the response of astrocytes to brain trauma which manifest opposite roles on brain injury repair. On the one hand, astrocytes undergoing astrogliosis inhibit tissue regeneration by forming scar tissue, but, on the other hand, they enhance damage repair through secretion of neuro-protecting and neurotrophic factors. Therefore, identifying means that regulate astrogliosis can provide a control over progression and repair of brain damage. We have previously shown that the calcium carbonate skeleton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 64 publications
0
12
0
Order By: Relevance
“…Reversely, an uncontrolled TBI may reversely disrupt this beneficial role through releasing inflammatory cytokines and spatial occupation. In chronic TBI, excessive astrogliosis can both enhance damage repair through secretion of neuroprotective and neurotrophic factors and inhibit tissue regeneration by forming scar tissue (Morad et al, ).…”
Section: Gfap and Neurological Diseasesmentioning
confidence: 99%
“…Reversely, an uncontrolled TBI may reversely disrupt this beneficial role through releasing inflammatory cytokines and spatial occupation. In chronic TBI, excessive astrogliosis can both enhance damage repair through secretion of neuroprotective and neurotrophic factors and inhibit tissue regeneration by forming scar tissue (Morad et al, ).…”
Section: Gfap and Neurological Diseasesmentioning
confidence: 99%
“…The aragonite crystalline surface of the coral skeleton is a strong adhesive substrate for various isolated cells in culture, including osteocytes, [24,25] mesenchymal stem cells, [26][27][28] neurons and glial cells [14,[18][19][20]22] as well as nervous tissue ex vivo. [21] This coralline biomaterial has a positive influence on these cells, increasing their survival [20] and activity.…”
Section: Csps Adhere To the Phagocytesmentioning
confidence: 99%
“…We have previously demonstrated that scaffolds derived from the skeleton of the corals Porites lutea and Trachyphyllia geoffroyi are adhesive and permissive for dissociated hippocampal neuronal tissue cultures . The scaffold nurtures the cells with its calcium ions, enhances the survival, growth and connectivity among the cultured neurons and elevates astrocytic hypertrophy . Thus the coral skeleton has considerable potential as an implant for tissue engineering of the nervous system …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…PDL enhances adherence of various cell types [19] including neurons and glia [20,21]. Indeed, PDL-coated coralline scaffolds (CS-PDL) are superior matrices for the cultivation of neural cells from the hippocampi of postnatal rat brains [8,[22][23][24][25][26]. Moreover, CS-PDL scaffolds are permissive and supportive for cultivated hippocampal tissue [23].…”
Section: Introductionmentioning
confidence: 99%